Methods of detection of the hidden indoctrinated information and psychological influences in information resources of the text content - Бараннік, В. В.; Белікова, Т. В.; Мусієнко, О. П.; Довбенко, О. В. (Science-based technologies, 2018)
The article deals with issues related to the processing of information resources to identify hidden suggestive effects. It is shown that the information and psychological impact is characterized by different semantic saturation. Therefore, special attention in the processing of information resources should be paid to the analysis of suggestive saturation, that is, the most important information on hidden information and psychological effects. The choice of technology of processing of information resources at which it will be possible to extract key information is proved. It is proposed to create systems to ensure information security of the state in the information space, as well as the need to use these methods of analysis of information resources to identify hidden suggestive effects. The variant of special software using the following methods is proposed.